INTER-LABORATORY COMPARE TEST IN THE FRAMEWORK OF INCREASING TRUST IN PHYSICS TESTING LABORATORIES OF ATK POLYTECHNIC - Eko Nuraini; Prasetyo Hermawan (Politek ATK Yogyakarta Press, 2022)
One of the raw materials for footwear is Chrome tanned box leather with a thickness according to the applicable SNI quality standards. The problem with measuring skin thickness has received less attention from laboratory personnel during testing. The Quality Control Section is responsible for the implementation of quality assurance and quality control of test results. External quality control is carried out by cross-laboratory comparisons. The purpose of this research is to find out the competence of the Physical Testing laboratory as an executor in inter-laboratory comparison tests with skin thickness test parameters. The material used is cow leather. The test method uses SNI-06-7128-2005. stationary. The comparative test was carried out from June to August 2022 followed by the Physical Testing Laboratory as the executor of the activities (laboratory A), laboratories B and C. The test results obtained standard deviation for laboratory A vs B 0.1396 and laboratory A vs C 0.0795 . The t value for laboratory A vs B was 0.625 and laboratory A vs C was 1.85. Based on t table at 95% confidence level for laboratory A vs B 2.228 and laboratory Avs C 2.201, t count < from t table comparative test between laboratories is declared not significantly different or acceptable. Physical Testing laboratory personnel can be declared competent for the skin thickness test.